IGI SERANG CITY'S STRATEGY TO IMPROVE TEACHER COMPETENCE - Utami, Maharani Windu; Maulida, Ratna Siti; Rohimat, Sonny; Zohriah, Anis; Muin, Abdul (STKIP Singkawang, 2025)
Education in Indonesia faces challenges in the form of unequal teacher quality and limited access to self-development. This condition is one of the responsibilities of professional teacher organizations mandated by law, specifically Law Number 14 of 2025 concerning Teachers and Lecturers. This study aims to analyze the strategies implemented by the Indonesian Teachers Association (IGI) of Serang City, as a professional teacher organization, in improving teacher competency. This study uses a qualitative approach with a case study method, analyzing IGI Serang City's strategies from August 2023 to July 2025. Data were collected through in-depth interviews, observations, and documentation studies. The results show that IGI Serang City implemented a comprehensive strategy focused on three main pillars: optimizing digital-based programs through regular webinars and online training reaching teachers from various regions; encouraging a culture of literacy and scientific publications by publishing three anthologies of teacher work; and maintaining direct interaction through offline activities such as workshops, training, and collaborations with various parties. This combination of online and offline strategies has proven effective in reaching a wider audience, offering flexibility, and building a productive learning community. The multidimensional strategy of IGI Serang City has not only succeeded in improving teachers' professional competence but also fostered a culture of sharing and scientific literacy, making it a relevant model for other teacher professional organizations.